2015
DOI: 10.1126/science.1260064
|View full text |Cite
|
Sign up to set email alerts
|

The type VI secretion system of Vibrio cholerae fosters horizontal gene transfer

Abstract: Natural competence for transformation is a common mode of horizontal gene transfer and contributes to bacterial evolution. Transformation occurs through the uptake of external DNA and its integration into the genome. Here we show that the type VI secretion system (T6SS), which serves as a predatory killing device, is part of the competence regulon in the naturally transformable pathogen Vibrio cholerae. The T6SS-encoding gene cluster is under the positive control of the competence regulators TfoX and QstR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
421
3
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 349 publications
(446 citation statements)
references
References 53 publications
12
421
3
5
Order By: Relevance
“…A second example is related to the T6SS of V. cholerae, which, in pandemic isolates of this species, has long been recognized as being silent under laboratory conditions (2). Borgeaud et al (12) discovered that chitin is a natural inducer of the T6SS in these strains (Fig. 1), consistent with the fact that many Vibrio species interact with and feed on natural chitinous surfaces.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…A second example is related to the T6SS of V. cholerae, which, in pandemic isolates of this species, has long been recognized as being silent under laboratory conditions (2). Borgeaud et al (12) discovered that chitin is a natural inducer of the T6SS in these strains (Fig. 1), consistent with the fact that many Vibrio species interact with and feed on natural chitinous surfaces.…”
supporting
confidence: 68%
“…1), consistent with the fact that many Vibrio species interact with and feed on natural chitinous surfaces. The authors further deciphered a regulatory link between T6SS induction and natural competence for transformation and demonstrated that T6SS-mediated interbacterial competition can be used by V. cholerae to acquire DNA from killed prey, thereby fostering horizontal gene transfer (12,13). These examples highlight the need to move research toward more realistic conditions that mimic the natural habitats of the bacteria under investigation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While we did not investigate any links between the aberrant biofilm phenotype and the upregulation of T6SS expression and activity in this study, it is interesting that LonA appears to play a regulatory role in both of these systems. Schwarz et al (71) showed that the T6SS is required for Burkholderia thailandensis to proliferate in a biofilm state when in the presence of Pseudomonas putida, and one study done with V. cholerae showed that T6SS expression and activity are upregulated when V. cholerae is allowed to form a biofilm on chitinous surfaces (71,72). While these studies do not imply that there is a direct regulatory connection between the T6SS and biofilm formation, they certainly suggest that the two processes are contextually related.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of T6SSs is usually induced by specific environmental signals such as temperature, salinity, cell density, and surface sensing and regulated by mainly the TCSs and by the QS, sRNA, c-di-GMP, cAMP-CRP, and alternative sigma factor systems (350, 713,716,[722][723][724][725][726][727], all of which are involved in the modulation of microbial surface colonization and in the regulation of gene expression in biofilms (414,728). The coordination of the TCS or the QS, sRNA, or c-di-GMP regulatory system with the expression of T6SSs may potentially aid in microbial surface colonization fitness via the displacement of competing bacteria at locations having growth-supportive conditions and via the promotion of horizontal gene transfer (718,729). For example, in V. cholerae, the expression of the T6SS is regulated by quorum-regulatory Qrr sRNAs, which repress the T6SS genes at low cell density (727).…”
Section: Deadly Competition: Chemical Agents Predation and Specialimentioning
confidence: 99%